Efficient Hydrogenation of CO2 to Methanol over Supported Subnanometer Gold Catalysts at Low Temperature. Issue 19 (7th August 2017) - Wu, Congyi; Zhang, Peng; Zhang, Zhaofu; Zhang, Lujun; Yang, Guanying; Han, Buxing
Abstract: Direct hydrogenation of CO2 to methanol under milder conditions is of great importance. The catalytic performances of Au particles with different sizes on various supports for this reaction were studied. It was demonstrated that catalytic properties of the catalysts depended both on size of Au particles and the composition of the supports. Au/ZrO2 with subnanometer Au particles (1.6 nm) had unprecedented high catalytic activity and excellent selectivity for the reaction, and methanol could be obtained even at 140 °C, which is obviously lower than those reported before. The outstanding performance of the Au/ZrO2 with subnanometer Au particles resulted from both the very small size of the Au particles and appropriate coupling between the Au particles and the support. Abstract : Go for gold : Supported subnanometer gold catalysts deliver good catalytic activity and selectivity in hydrogenation of CO2 to methanol at low temperature. The combination of zirconia and the gold particles shows the best catalytic performance, with selectivity to methanol up to 73 % at 180 °C.